Ways of increasing the efficiency of treatment of patients with non-alcoholic fat liver with liver’s disease - Zabolotna, I. B. (Journal of Education, Health and Sport, 2017)
The article presents experimental data on the effectiveness of the internal use of the aqueous solution of Poltava bischofite in rats with a model of nonalcoholic fatty liver disease. The obtained experimental data substantiated the use of "Poltava bischofite" in patients with nonalcoholic fatty liver disease with concomitant pathology of the digestive system. The expediency of the internal course application of the "Poltava bischofite" solution in patients with nonalcoholic fatty liver disease with concomitant pathology of the digestive organs is proved. As a result of clinical trials, the clinical course of the main and accompanying diseases of the digestive system was improved, the functional state of the liver restored, the signs of dyslipidemia and insulin resistance decreased.